THE MODEL OF OPEN PRICE CONTRACTS UNDER THE VIENNA CONVENTION, SOFT LAW AND LITHUANIAN CONTRACT LAW - Bublienė, Danguolė; Dumčiuvienė, Daiva (Teisė, 2016)
The article examines the issue of open price contracts. The article aims to assess how open price contracts are approached in the CISG and how the concept of open price have been changed from the adoption of this instrument till the presentation of the Proposal for a Regulation on a Common European Sales Law. The model established in the Lithuanian contract law and developed by court practice is the object of this article as well. Open price contracts are analysed by examining the rules related to the definition of an offer and contract, the aspects of the contract content and the determination of price.